Photochemistry of hydrogen bonded heterocycles probed by photodissociation experiments and ab initio methods - Slavíček, Petr; Fárník, Michal (Physical chemistry chemical physics, 2011)
In this perspective article, we focus on the photochemistry of five-membered nitrogen containing heterocycles (pyrrole, imidazole and pyrazole) in clusters. These heterocycles represent paradigmatic structures for larger biologically active heterocyclic molecules and complexes. The dimers of the three molecules are also archetypes of different bonding patterns: N-H···π interaction, N-H···N hydrogen bond and double hydrogen bond. We briefly review available data on photochemistry of the title molecules in the gas phase, but primarily we focus on the new reaction channels opened upon the complexation with other heterocycles or solvent molecules. Based on ab initio calculations we discuss various possible reactions in the excited states of the clusters: (1) hydrogen dissociation, (2) hydrogen transfer between the heterocyclic units, (3) molecular ring distortion, and (4) coupled electron-proton transfer. The increasing photostability with complexity of the system can be inferred from experiments with photodissociation in these clusters. A unified view on photoinduced processes in five-membered N-heterocycles is provided. We show that even though different deactivation channels are energetically possible for the complexed heterocycles, in most cases the major result is a fast reconstruction of the ground state. The complexed or solvated heterocycles are thus inherently photostable although the stability can in principle be achieved via different reaction routes.
Keywords: Imidazoles; Photolysis; Pyrroles; vodík; imidazoly; Hydrogen; fotochemie; Pyrazoles; vodíková vazba; fotolýza; pyrroly; molekulární modely; Heterocyclic Compounds; heterocyklické sloučeniny; Models, Molecular; dimerizace; Photochemistry; Dimerization; pyrazoly; Hydrogen Bonding